Equity Risk Premium in ASEAN: Empirical Analysis on Its Puzzle (Asian Business Research, 2017)
This paper aims to mainly investigate equity risk premium of the six major members of ASEAN countries such as Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam which have been chosen based on their stock market development and data availability. It has focused on the two main issues of the equity risk premium such as the intriguing issue on the existence of equity premium puzzle and the analysis on the impact of the 2008 financial crisis on the trend of the equity risk premium and their potential contribution on the risk aversion's attitude of the ASEAN investors. Three methods are utilized to test this phenomenon (1) basic model consumption of Mehra and Prescott (1985) and simplified model by Ni (2006); (2) calibration (Campbell, 2003) and (3) GMM estimation (Hansen, 1982). The calibration method results suggest that the puzzle exists in Indonesia.It has determined that the puzzle seems lying on the negative covariance between the consumption growth rate and the average real stock return. After applying GMM as method of the three sub-sample analyses for before, after and excluding 2008, it shows that financial crisis didn't affect much the value of risk aversion, but it cannot deny the fact that it has profound effect on the behavior of the equity risk premium. It can also be inferred that after crisis, ASEAN investors are likely tend to become more decreasing relative risk averse and prefer to have happiness tomorrow than today.